Regards croisés sur l’action diplomatique française en Amérique latine : le voyage de Louis Jacquinot (1958) - Alvar de La Llosa (Caravelle)
The visit of Jacquinot, a high-ranking civil servant, to South America in 1958 heralded a new orientation in France’s foreign policy towards Latin America, at a time when the election of de Gaulle to French Presidency allowed for a solution of the troubles in the French North African colony of Algeria, thus paving the way to new diplomatic activities. To a certain extent, this visit also revealed expectations concerning economic development in this hemisphere, prior to the Cuban Revolution. The visit proved to be an opportunity for economically emerging countries −such as Brazil or Argentina− to benefit from new sources of credit and investments, thus leading them to develop a network of new diplomatic relations with a variety of countries rather than being forced to deal exclusively with Washington. Mexico fearfully views what it takes to be a french attempt to establish once again a « pan-latin » unity.